2015
DOI: 10.1016/j.jphotobiol.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

A dietary supplement improves facial photoaging and skin sebum, hydration and tonicity modulating serum fibronectin, neutrophil elastase 2, hyaluronic acid and carbonylated proteins

Abstract: We found significantly increased serum levels of neutrophil elastase 2, elastin and carbonylated proteins and decreased levels of hyaluronic acid and fibronectin in patients affected by facial photoaging, if compared with healthy controls. These findings coupled with a significant decrease in skin hydration, tonicity and elasticity and increased skin pH and sebum. Treatment with the dietary supplement VISCODERM Pearls significantly improved VAS photoaging score and skin hydration, sebum and tonicity 2 weeks af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 72 publications
1
34
0
Order By: Relevance
“…Blood contains several kinds of extracellular matrix proteins, such as fibronectin, fibrinogen, type IV collagen, vitronectin, and elastin, all of which except fibrinogen are contained in both plasma and serum (39)(40)(41). It has been reported that some of the cell surface proteins of S. aureus bind and aggregate following interaction with extracellular matrix proteins in the blood (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Blood contains several kinds of extracellular matrix proteins, such as fibronectin, fibrinogen, type IV collagen, vitronectin, and elastin, all of which except fibrinogen are contained in both plasma and serum (39)(40)(41). It has been reported that some of the cell surface proteins of S. aureus bind and aggregate following interaction with extracellular matrix proteins in the blood (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the diagnostic device encompasses impedance variation as related to intracellular and interstitial water content. Therefore, total, extracellular and intracellular water can be detected [23].…”
Section: Thickness Of the Stratum Corneum (Sct)mentioning
confidence: 99%
“…Modulation of these parameters by the dietary supplementation may be useful to counteract some of the age-related dermatological changes, accordingly with previous findings, where the same supplement significantly improved VAS photoaging score, facial sebum, hydration and tonicity from the second week of treatment. 24 Collagen was added into the formula since experimental evidences from murine models has shown that: if adequately orally administered it prevents UV radiationinduced skin damage. 35,36 In a study by Proksch et al, oral supplementation of collagen hydrolysate composed of specific collagen peptides (2.5 g/d or 5.0 g/d for 8 weeks) increased skin elasticity in middle-aged women after 4 weeks of supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…24 The object of this second study is to confirm that this supplement affects several skin face parameters [i.e. hydration, trans epidermal water loss (TEWL) and elasticity] and to confirm the hypothesis that it can also improves nails hardness, hair loss and hair breakage in patients affected by age-related dermatological changes.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation